Carne de ave desossada mecanicamente - Voloch Rozenberg, Tília; Salustiano Pereira, Alonso (Revista Ceres, 2025)
With the mechanical deboning poultry process, bones crushed with the meat left after manual deboning are forced through a sieve. Meat and some bone marrow pass through the sieve and are thus separated from the bone residue. The resultant meat paste is called mechanically deboned poultry meat (MDPM). MDPM is characterized by its paste-like consistency and high susceptibility to deteriorative changes which occur during storage. The extreme stress and aeration during the process and the compositional nature of the product (bone marrow, heme, and lipids) contribute to its high oxidative potential. However, MDPM has various economical and social advantages, and the potential problems could be overcome with research and quality control.